PERAN GOOD CORPORATE GOVERNANCE DALAM MENINGKATKAN KINERJA KEUANGAN PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2017-2019 - Ichmahtul Hidayah; Melati Oktafiyani (Universitas Dian Nuswantoro, 2023)
Financial performance is often associated with the level of achievement of company profits. Profit is used as a measure of the extent to which a company can implement the company's strategy which is used as a basis for analysis by investors in making decisions. The existence of a performance appraisal assists companies in developing corporate strategies to maximize performance and achieve company targets in increasing returns for shareholders. Therefore, this study aims to empirically examine the determinants of financial performance in terms of good corporate governance through managerial ownership, institutional ownership, independent commissioners and audit committees. Based on the purposive sampling method, this research has 17 mining companies listed on the IDX in 2017-2019. SPSS version 20 is a tool used for data processing to then be analyzed using multiple linear regression analysis. The findings of this study indicate that managerial ownership variables affect financial performance, while institutional ownership, independent board of commissioners and audit committee variables do not affect financial performance.